Pork skin-based emulsion gels as animal fat replacers in hot-dog style sausages - Santos, Mirian dos; Munekata, Paulo E. S.; Pateiro, Mirian; Magalhaes, Giseli Carvalho; Silva Barretto, Andrea Carla [UNESP]; Manuel Lorenzo, Jose; Rodrigues Pollonio, Marise Aparecida (Elsevier B.V., 2020)
Pork skin-based emulsion gels (EGs) elaborated with canola oil, bamboo fiber and inulin were used to replace 50% and 100% of pork back fat in hot-dog sausages made with a high content of mechanically deboned chicken meat (MDCM). Nutritional, technological, and microstructural characteristics of sausages were assessed. Sausages containing EGs presented a higher amount of 0)3 polyunsaturated fatty acids (PUFAs), and reduction of saturated fatty acids (SFAs) and 0)6/0)3 ratio up to 77% and 76%, respectively. pH, aw, and texture parameters of sausages were not affected by EGs addition. Color parameters presented a lightly increase in L* values and a reduction in a* values in the sausages. The replacement of 50% of pork back fat by EGs did not affect all sensory parameters of sausages. Thus, we concluded that pork skin-based EGs are promising alternatives to replace pork back fat in low-cost sausages.
Keywords: Canola oil; Bamboo fiber; Inulin; By-products; Value-added